Metformin alleviates oxidative stress‐induced senescence of human lens epithelial cells via AMPK activation and autophagic flux restoration. Issue 17 (23rd July 2021) - Chen, Mengmeng; Zhang, Chunmei; Zhou, Nan; Wang, Xu; Su, Dongmei; Qi, Yanhua
Abstract: Cataracts are the leading cause of blindness worldwide owing to the increasing proportion of elderly individuals in the population. The purpose of this study was to investigate whether metformin could alleviate the occurrence and development of age‐related cataract (ARC) and the underlying mechanism. In the present study, we established a senescence model induced by oxidative stress, which was confirmed by measuring β‐galactosidase activity, qRT‐PCR and Western blotting. In addition, we showed that metformin alleviated the oxidative stress‐induced senescence of HLE‐B3 cells via the activation of AMPK. Next, we provided evidence that oxidative stress impaired autophagic flux and induced lysosomal dysfunction. Subsequently, we found that metformin restored autophagic flux that had been impaired by oxidative stress by activating AMPK. Additionally, we found that metformin suppressed HLE‐B3 cell senescence by improving lysosomal function and inactivating mTOR. Furthermore, the inactivation of AMPK, impairment of autophagic flux and lysosomal dysfunction were observed in the human lens epithelium of ARC. In summary, our data suggest that the activation of AMPK may be a potential strategy for preventing ARC, and metformin may be an emerging candidate to alleviate the formation and development of ARC.